2011
DOI: 10.1371/journal.pone.0021598
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control in Adolescence: Neural Underpinnings and Relation to Self-Report Behaviors

Abstract: BackgroundAdolescence is commonly characterized by impulsivity, poor decision-making, and lack of foresight. However, the developmental neural underpinnings of these characteristics are not well established.Methodology/Principal FindingsTo test the hypothesis that these adolescent behaviors are linked to under-developed proactive control mechanisms, the present study employed a hybrid block/event-related functional Magnetic Resonance Imaging (fMRI) Stroop paradigm combined with self-report questionnaires in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
100
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 85 publications
17
100
0
1
Order By: Relevance
“…Response sequence planning continued to develop after 7 as shown by increasing differences between the preparatory intervals and subsequent item recall durations with advancing age, especially for the longest sequences. Consistent with these findings, although children start to engage proactive control from about 6 years of age, proactive control continues to increase through early adulthood on other executive control measures (Andrews-Hanna et al, 2011; Waxer & Morton, 2011). …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Response sequence planning continued to develop after 7 as shown by increasing differences between the preparatory intervals and subsequent item recall durations with advancing age, especially for the longest sequences. Consistent with these findings, although children start to engage proactive control from about 6 years of age, proactive control continues to increase through early adulthood on other executive control measures (Andrews-Hanna et al, 2011; Waxer & Morton, 2011). …”
Section: Discussionsupporting
confidence: 60%
“…Response planning is a critical feature of proactive control (Andrews-Hanna et al, 2011; Killikelly & Szűcs, 2013; West, Bailey, Tiernan, Boonsuk, & Gilbert, 2012). Its contribution to working memory can be measured through recall item duration, that is, the time that elapses between the recall of two successive items.…”
mentioning
confidence: 99%
“…Concerning (iii), adolescents' cognitive control capabilities related to impulse control, foresight, and resistance to peer pressure may not have fully developed (Andrews-Hanna et al, 2011), indicating that the adolescents may lack introspective ability to comprehend potentially problematic Internet usage.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that, when asked to respond to specific cue-target associations, 3-year-olds show greater late mental effort (as shown by greater pupil dilation) after target onset, showing no anticipation of the target, whereas 8-year-olds show greater early mental effort before target onset; suggesting a shift from reactive to proactive control during childhood. The shift to proactive control seems to occur around 6 years of age, although proactive control continues to develop through late adolescence (Andrews-Hanna et al, 2011; Chatham, Provan, & Munakata, in revision; Chevalier & al., 2014; Lucenet & Blaye, 2014). Understanding the reasons why young children do not engage the most mature and efficient forms of control is critical to uncover the mechanisms underpinning executive control development and to design effective interventions early in childhood.…”
mentioning
confidence: 99%